2001
DOI: 10.1177/0044118x01033002002
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Effectiveness of Adolescent Substance Abuse Treatment Models

Abstract: Recent reports describe alarming trends of adolescent drug use and a lack of treatment for substance use disorder symptoms. Early efforts in adolescent treatment relied on adult models that may not have considered the unique needs of adolescents. Recently, there has been an increased emphasis in developing intervention models designed specifically for adolescents. This article provides descriptions of current approaches to adolescent substance abuse treatment and summaries of research assessing the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 31 publications
0
76
0
6
Order By: Relevance
“…At the top of the public health pyramid, targeted services for CEV would be used for the minority of children who have prolonged adjustment problems related to violence exposure. There is a growing evidence base about what works in terms of the moreintensive services for children with PTSD (Foa, Keane, et al, 2008), depression (Michael and Crowley, 2002), and substance abuse problems (Muck et al, 2001;Tevyaw and Monti, 2004). Further, studies of interventions for maltreated children have found medium to large effects on child behavior (Skowron and Reinemann, 2005;Barlow et al, 2006) and medium to large effects on PTSD (Macdonald, Higgins, and Ramchandani, 2006;Rolfsnes and Idsoe, 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…At the top of the public health pyramid, targeted services for CEV would be used for the minority of children who have prolonged adjustment problems related to violence exposure. There is a growing evidence base about what works in terms of the moreintensive services for children with PTSD (Foa, Keane, et al, 2008), depression (Michael and Crowley, 2002), and substance abuse problems (Muck et al, 2001;Tevyaw and Monti, 2004). Further, studies of interventions for maltreated children have found medium to large effects on child behavior (Skowron and Reinemann, 2005;Barlow et al, 2006) and medium to large effects on PTSD (Macdonald, Higgins, and Ramchandani, 2006;Rolfsnes and Idsoe, 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…L'approche cognitive-comportementale met l'accent sur les processus cognitifs et les croyances reliés à la consommation de l'adolescent (Muck et al, 2001). Selon cette approche, la consommation de SPA est un comportement appris, initié et maintenu par des facteurs environnementaux (Cottraux, 2004).…”
Section: Recommandations Cliniques En Fonction De La Trajectoireunclassified
“…Selon cette approche, la consommation de SPA est un comportement appris, initié et maintenu par des facteurs environnementaux (Cottraux, 2004). Ainsi, pour conclure à une démar-che de réadaptation réussie, le jeune doit désapprendre ses comportements pour en apprendre de nouveaux, alternatifs à la consommation, et qui sont socialement acceptés (Muck et al, 2001). L'objectif de l'approche cognitive-comportementale est donc que le jeune acquiert de nouvelles compétences qui lui permettront d'affronter les diffi cultés de la vie courante sans avoir recours à la consommation de SPA (Phan et Bastard-Dagher, 2006).…”
Section: Recommandations Cliniques En Fonction De La Trajectoireunclassified
“…According to Jessor and his colleagues, adolescents' substance abuse problems are often embedded within a larger category described as "problem behavior syndrome" (Jessor, van den Bos, Vanderryn, Costa & Turbin, 1995), where other problematic behaviors such as risky unsafe sexual behavior, conduct problems, delinquency and academic failure often co-occur . Many of the existing empirical studies that report samples of clinically diagnosed adolescents have been drawn from adjudicated juvenile justice populations (Muck, Zempolich, Titus, & Fishman, 2001). One reason for this is the strong association found between delinquency-related problem behaviors and substance abuse.…”
Section: Substance Abusing Hispanic Youthsmentioning
confidence: 99%
“…Adolescents frequently deny they have any substance abuse problems, even lying about whether they use at all or not (Muck, et al, 2001;Pabon, 2005;Campbell, Weisner, & Sterling, 2006).…”
Section: Substance Abusing Hispanic Youthsmentioning
confidence: 99%